2011
DOI: 10.1087/20110204
|View full text |Cite
|
Sign up to set email alerts
|

Citing data sources in the social sciences: do authors do it?

Abstract: It is expected that authors will provide citations for all papers referenced in their writings. The necessity of providing citations for data is not so widely recognized. Proponents of the data‐sharing movement have advocated the citation of datasets in order to recognize contributions and enhance access. This study examines a sample of papers from the Inter‐University Consortium for Political and Social Research (ICPSR) Bibliography of Data‐Related Literature that are based on secondary analysis of datasets a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 20 publications
1
43
0
Order By: Relevance
“…I used data citation tracking to identify people who have used data from these repositories for their research. Currently, as no consistent standard for citing data has yet been established (Mooney 2011), tracking data citations is a challenging process. In addition, perhaps because a number of articles use data without citing them (Mooney 2011), the use of citation tracking to identify users might be a limitation of this sampling plan.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…I used data citation tracking to identify people who have used data from these repositories for their research. Currently, as no consistent standard for citing data has yet been established (Mooney 2011), tracking data citations is a challenging process. In addition, perhaps because a number of articles use data without citing them (Mooney 2011), the use of citation tracking to identify users might be a limitation of this sampling plan.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, as no consistent standard for citing data has yet been established (Mooney 2011), tracking data citations is a challenging process. In addition, perhaps because a number of articles use data without citing them (Mooney 2011), the use of citation tracking to identify users might be a limitation of this sampling plan. Even though data citation tracking has limitations, it is still the most effective way to identify users of datasets from each repository.…”
Section: Methodsmentioning
confidence: 99%
“…(p. 4) There is a clear gap between policy and citation practices for data sets. One small-scale study found that 61 percent of the articles reviewed failed to provide even informal citation of the underlying data (Mooney, 2011). Similarly, a study of recently published articles in high-impact journals found that in the majority of cases, data to replicate articles was not clearly identified nor made available in a manner consistent with the policies of the publishing journal (Alsheikh-Ali et al, 2011).…”
Section: Social-cultural Researchmentioning
confidence: 99%
“…Sieber and Trumbo (1995) investigated the citation of the General Social Survey, one of the most important social science surveys in the United States, and found that less than twenty percent of authors included survey in-structure citation, and nine omitted any mention at all of the data source. Mooney (2011) analyzed a nonrandom sample of 49 journal articles representing 39 journals and 33 data set series and found that 61 percent failed to provide any type of citation. ICPSR's (2011) description of the methodology required to generate its "Bibliography of Data Related Literature" illustrates both the high degree of manual effort and the many specific challenges of identifying data use within current publications.…”
Section: Evaluation Researchmentioning
confidence: 99%
“…For centuries, scholars have been expected to cite the evidence, theories, and conclusions on which their own research builds. Notwithstanding this long tradition, social science editors and publishers have been slow to recognize that data are intellectual products for which citation should be required (Mooney 2011 Funding agencies are also using data citation as a way to demonstrate the impact of their data collection investments. For example, in 2012, the ANES began to require people who download data from its website to sign an agreement to formally cite the ANES in any and all intellectual products they derive from its data.…”
Section: Data Sharingmentioning
confidence: 99%